Effect of soil texture and water application rate on water movement in soil profile under trickle irrigation - Kaiser Ibrahim (University of Thi-Qar Journal of Science, 2019)
the study was conducted to know the effect of water application rate (R) and soil texture (S)on vertically and horizontally movement of water in the soil profile under triclcle irrigationtwo type of soil texture (S1 sandy Loam, S2 Loamy soil ) and three water application rate(R1=0.5 L/h, R2=1.0 L/h and R3= 1.5 L/h) was used.The used soil was in plastic container(80*80)cm with plexiglass in one side of container to show the vertically movement ofwater clearly . The results were showed that the horizontal wet front increases withincreasing the water application rate in the Loam soil as compard with sandy loam soil , butthe vertically distance of wet front at the sandy loam was more than the same distance at theloam soil . The Philip (1958) one and two term equation used to fit the experimental data ofwet front distance with time.Emperical equation that describe this movement were also used for the all treatment.